CULTIVATING A GARDEN OF NAMES IN THE CAPE HORN MINIATURE FORESTS: EXTENDING BIOCULTURAL CONSERVATION AND ETHICS TO LITTLE PERCEIVED LIVING BEINGS - Lewis, Lily; Gottschalk-Druschkec, Caroline; Saldias, Camila; Mackenzie Calderon, Roy; Malebran, Javiera; Goffinet, Bernard; Rozzi Marin, Ricardo Roberto (My University, 2018)
Bryophytes (mosses, liverworts, and hornworts) and lichens have been undervalued in conservation and environmental education programs, and by modern culture in general. So much so, that most bryophytes and lichens lack a common name. We present a new methodology and activity to foster an ecological understanding of biodiversity, as well as of biocultural conservation and ethics, which includes little, under-perceived, living-beings --such as bryophytes. If something has no name, it does not exist in the cultural realm. If something is named, then it exists in the cultural sphere; additionally, its existence is decisively influenced by its name. At the southern end of the Americas, the UNESCO Cape Horn Biosphere Reserve in Chile protects a world's biodiversity hotspot for bryophytes. Here, the research team at the Omora Ethnobotanical Park has developed an innovative educational and ecotourism activity to appreciate bryophytes: Cultivating a garden of names. This activity has been developed with the methodological approach of Field Environmental Philosophy. It encourages students and park's visitors to engage physically as well as culturally (including the symbolic-linguistic dimension) with bryophytes and lichens, their life-habits and habitats. Park's visitors are invited to observe, draw, and create names for bryophytes and lichens by using: (i) a magnifying glass or hand-lens to amplify the biophysical features of small plants, and (ii) the conceptual lenses of the biocultural ethics to broaden their understanding about how to interpret and respect the natural world. Through this activity, visitors connect to living beings that were previously under-perceived, and they come to see, value and care for a biophysical reality that is diverse, beautiful, and performs ecological functions that are essential to ecosystem integrity and human well-being. Cultivating a garden of names fosters a change of scientific and ethical perspectives to include little-perceived groups of organisms into the goals of conservation and environmental education.
Keywords: bryophytes; biocultural ethics; education; field environmental philosophy; lichens